Parasite infracommunities of leporinus friderici: A comparison of three tributaries of the jurumirim reservoir in southeastern Brazil - Yamada, Fábio Hideki [UNESP]; Bongiovani, Marcela F. [UNESP]; Yamada, Priscilla O. F. [UNESP]; Da Silva, Reinaldo J. [UNESP] (FapUNIFESP (SciELO), 2017)
The degradation and homogenization of natural habitats is considered a major cause of biotic homogenization. Many studies have been undertaken on the effects of dams on aquatic wildlife, in particular fish assemblages. But how do dams affect the parasitic fauna of such fish? The aim of the present study was to examine parasitic similarity, comparing the diversity and structure of parasite communities of Leporinus friderici (Characiformes, Anostomidae) in three upstream tributaries under the influence of the Jurumirim Dam on the Upper Paranapanema River in southeastern Brazil. The present study did not find any significant differences in parasite communities among populations of L. friderici in the three upstream tributaries. This result highlights that dams promote and facilitate the dispersal of organisms between localities, and therefore the spatial homogenization of parasite communities. Overall, the results suggest that fish parasite assemblages can provide suitable data for evaluating biotic homogenization caused by dams.
Keywords: Leporinus friderici; Metazoan parasites; Neotropical region; Similarity; Watershed conservation